STRATEGI GURU PAUD DALAM MENERAPKAN PEMBELAJARAN DEEP LEARNING BERBASIS ALAT PERMAINAN EDUKATIF PARAGA HEWAN DI KB CERIA BANDAR - Sumiati, Sumiati; Suprayitno, Kabul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies of early childhood education (PAUD) teachers in implementing deep learning-based instruction using animal prop educational play tools at KB Ceria Bandar. A qualitative descriptive approach was employed, with PAUD teachers as the research subjects. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The study focuses on teacher strategies in planning, implementation, and evaluation, as well as supporting and inhibiting factors. The findings reveal that teachers apply systematic strategies in three stages. In the planning stage, activities are designed based on themes and children's characteristics. During implementation, teachers act as facilitators who encourage exploration and meaning-making through play. In the evaluation stage, continuous assessment is conducted on children’s development. The use of educational play tools enhances engagement, understanding, and learning quality. Supporting factors include teacher creativity and student enthusiasm, while limitations involve inadequate facilities and teachers’ understanding of deep learning concepts.